2014
DOI: 10.1149/2.102406jes
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Felt Coated with Titanium Dioxide/Carbon Black Composite as Negative Electrode for Vanadium Redox Flow Battery

Abstract: This investigation focuses on the effect of titanium dioxide (TiO 2 ) coatings of a carbon black (XC-72) negative electrode on the performance of a vanadium redox flow battery (VRFB). TiO 2 , a hydrophilic material, was added to the carbon electrode to improve the wettability and reduce the electrical resistance of the electrode surface. The electrochemical performances of homemade TiO 2 , commercial TiO 2 , and carbon felt are investigated by using cyclic voltammetry and single-cell charge-discharge measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 26 publications
2
27
1
1
Order By: Relevance
“…[24,25] In this scenario, TiO 2 is au seful materialf or photocatalysis, [26] gas sensors, [27][28][29] Li-ion batteries, [30,31] and catalysis. [34][35][36] Ts eng et al [37,38] explored the effect of the anatase-TiO 2 nanoparticles deposited on carbon black as an egative electrode in VRFBs. Over the past decade, DFT predictions, in conjunction with experimental efforts, have played an important role in designing electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24,25] In this scenario, TiO 2 is au seful materialf or photocatalysis, [26] gas sensors, [27][28][29] Li-ion batteries, [30,31] and catalysis. [34][35][36] Ts eng et al [37,38] explored the effect of the anatase-TiO 2 nanoparticles deposited on carbon black as an egative electrode in VRFBs. Over the past decade, DFT predictions, in conjunction with experimental efforts, have played an important role in designing electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 dramatically reduces the HER rate by several orders of magnitude. [34][35][36] Ts eng et al [37,38] explored the effect of the anatase-TiO 2 nanoparticles deposited on carbon black as an egative electrode in VRFBs. Owing to the partial reduction of HER activity that was obtained, the electrocatalyst containing TiO 2 nanoparticlese xhibitede xcellent resultsi nc omparison with commercial electrodese ven at high current densities.…”
Section: Introductionmentioning
confidence: 99%
“…For VRFBs, carbon-based electrodes based on graphite felts [5] meet most requirements including high electrical conductivity (at least under compression), availability and price. [6] However, it was also shown that this standard electrode material (carbon felt/carbon nonwoven) has to be activated in order to provide an acceptable catalytic activity for vanadium ion redox conversion, [7] and even in this case further improvement is desired to overcome kinetic limitations, as detailed above.…”
Section: Introductionmentioning
confidence: 99%
“…However, the performance is less than satisfactory due to the poor electrochemical activity and low surface area of the electrodes, which will cause high polarization loss on the charge/discharge processes during battery operations . To tackle this problem, various approaches including surface treatment and depositing catalysts have been proposed to improve the activity and specific surface area of the electrodes . Nevertheless, a majority of the surface modifications were conducted under elevated temperature or chemical baths by introducing strong acids and alkalis (HNO 3 , H 2 SO 4 , KOH) .…”
Section: Introductionmentioning
confidence: 99%